Effects of family planning service utilization determinants on unmet need incidents with generalized structural equation modelingAJOG Global Reports at a Glance - Ayudina Larasanti, MPH; Dumilah Ayuningtyas, Dr, MHA (Elsevier, 2022)
BACKGROUND: One of the reasons for the lack of optimal achievement in terms of contraceptive use in Indonesia is the unmet need for family planning that has not been fully addressed. OBJECTIVE: This study aimed to determine the direct, indirect, and total effect of the determinants of family planning services utilization on the incidence of unmet need spacing and limiting in Indonesia to provide a basis for appropriate and effective program recommendations. STUDY DESIGN: This study used secondary data from the 2017 Indonesian Demographic and Health Survey with a cross-sectional design with 33,635 respondents who were married women aged 14 to 49 years. RESULTS: The results of the generalized structural equation modeling showed that the incidence of unmet need in Indonesia was 11.68%, consisting of unmet need spacing (4.86%) and unmet need limiting (6.82%). The quality of family planning services had a positive indirect effect on the incidence of unmet need spacing. The quality of family planning services also had a positive direct, indirect, and total effect on the incidence of unmet need limiting. Socioeconomic and demographic status variables had a negative direct effect on the incidence of unmet need spacing, whereas the indirect and the total effect were positive. The direct and total effect of socioeconomic and demographic status variables on the incidence of unmet need limiting were positive. The women's autonomy variable had a positive direct, indirect, and total effect on the incidence of unmet need spacing. Women's autonomy had positive indirect and total effect on the incidence of unmet needs limiting. The variable of access problems did not have a significant effect on the incidence of unmet need spacing and unmet need limiting. The ideal number of children had a negative direct and total effect on the incidence of unmet need spacing and unmet need limiting in Indonesia. CONCLUSION: The variables that have been shown to have a significant effect on the incidence of unmet needs were the quality of family planning services, socioeconomic and demographic status, women's autonomy, and the ideal number of children.